2006
DOI: 10.1002/elan.200503419
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Layer Correction for Electron‐Transfer Kinetics at Glassy Carbon and Mercury Electrodes in N,N‐Dimethylformamide

Abstract: The double-layer properties of the glassy carbon electrode in N,N-dimethylformamide (DMF) containing tetrabutylammonium perchlorate (TBAP) at different concentrations have been studied by cyclic voltammetry and impedance. The results were compared with analogous results obtained for the mercury/DMF interface. For both electrodes, the double-layer data were treated to obtain useful equations describing the dependence of the outer Helmholtz plane potential on the applied potential. The kinetics of the dissociati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 43 publications
(34 reference statements)
1
27
0
Order By: Relevance
“…The working electrode was a 0.55 mm radius glassy carbon disk prepared, stored, and activated as already described . A Pt wire was the counter electrode.…”
Section: Methodssupporting
confidence: 81%
“…The working electrode was a 0.55 mm radius glassy carbon disk prepared, stored, and activated as already described . A Pt wire was the counter electrode.…”
Section: Methodssupporting
confidence: 81%
“…The values discussed above were obtained by neglecting double‐layer effects. In fact, the characterization of the double‐layer properties of GC was carried out only very recently, by applying the Gouy–Chapman–Stern double‐layer theory 22. Application of such a correction, whose effect depends on the explored potential range and the potential region to which the experimental α or k het data need to be extrapolated, does not change substantially the estimates of Table 2: typically, the E ° values become slightly more positive (the experimental error in the estimated E ° of “slow” DET acceptors is already on the order of 0.1 V), the log ${k{{{\circ}\hfill \atop {\rm het}\hfill}}}$ values increase by 0.4–0.6 units and the intrinsic barriers decrease by 0.6–0.8 kcal mol −1 , but the contribution of (Δ${G{{{\ne}\hfill \atop 0{\rm \char44}{\rm i}\hfill}}}$ ) het to the latter decreases by no more than 5 %.…”
Section: Resultsmentioning
confidence: 99%
“…The GC electrodes were stored in ethanol and were polished before experiments with a 0.25 μm diamond paste (Struers) and ultrasonically rinsed with ethanol for 5 min. The electrodes were electrochemically activated in the background solution by means of several voltammetric cycles at 0.5 V s −1 between the anodic and cathodic solvent/electrolyte discharges, until the quality features described in reference 22 were obtained. The electrode area was determined by measuring the limiting convoluted current of ferrocene, whose diffusion coefficient in DMF is 1.13×10 −5 cm 2 s −1 23.…”
Section: Methodsmentioning
confidence: 99%
“…CV was carried out in DMF, acetonitrile (ACN), and dichloromethane (DCM) in the presence of 0.1 M tetra‐ n ‐butylammonium perchlorate (TBAP) as the supporting electrolyte, using a properly activated glassy carbon electrode . The CVs of compounds 2 0 – 5 , which are exemplified in Figure for ACN, show that (i) the reduction is chemically reversible, (ii) the E ° shifts positively as n H increases, and (iii) an increase of the peptide length causes a decrease of the peak current.…”
Section: Resultsmentioning
confidence: 99%
“…(9)], yielding ERCOOOtBu/BuO,RCOO-=-0.14V . As the double‐layer properties of glassy carbon in ACN are unknown (only for DMF data are available) the α values could not be corrected for the double‐layer effect. However, we previously showed that this correction is indeed quite small at the investigated potentials …”
Section: Resultsmentioning
confidence: 99%